Synthesis and crystal structure of 7-(diethylamino)-2-ethoxy-3-(4-nitrophenyl)- 2H-benzo[e] [1,2]oxaphosphinin 2-oxide - Kulai, I. V.; Mallet-Ladeira, S.; Kovtunenko, V. A.; Voitenko, Z. V. (Reports of the National Academy of Sciences of Ukraine, 2015)
A new member of 3-aryl phosphacoumarins has been synthesized by the Knoevenagel condensation of 4-(diethylamino)salicylaldehyde and diethyl 4-nitrobenzylphosphonate and the further cyclization. The title compound was fully characterized by NMR spectroscopy, high-resolution massspectrometry, and single crystal X-ray diffraction. Comparison of the molecular structures of synthesized phosphacoumarin and analogous coumarin is made by basing on the obtained data. Main structure features of the benzo[e] [1,2]oxaphosphinin fragment were analyzed in terms of the phosphorus influence.